2016
DOI: 10.3390/su9010003
|View full text |Cite
|
Sign up to set email alerts
|

Social Innovation and Sustainable Rural Development: The Case of a Brazilian Agroecology Network

Abstract: Abstract:Food is central to human beings and their social life. The growing industrialization of the food system has led to a greater availability of food, along with an increasing risk perception and awareness in consumers. At the same time, there is an increasing resistance from citizens to the dominant model of production and a growing demand for healthy food. As a consequence, an increasing number of social networks have been formed worldwide involving the collaboration between producers and consumers. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 8 publications
1
57
0
11
Order By: Relevance
“…In addition, in line with other research, the academic training of the manager is a clear factor explaining the economic efficiency of the organization [18][19][20][21][22]. On the other hand, many authors emphasize the relevance of innovation in organizational performance [33][34][35][36]. Specifically, there is a clear consensus that the organizational use of new technologies will be a clear determinant of their efficiency [38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, in line with other research, the academic training of the manager is a clear factor explaining the economic efficiency of the organization [18][19][20][21][22]. On the other hand, many authors emphasize the relevance of innovation in organizational performance [33][34][35][36]. Specifically, there is a clear consensus that the organizational use of new technologies will be a clear determinant of their efficiency [38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 87%
“…The adoption of innovations in business is fundamental for company development and growth [34], as well as for attaining competitive advantage [35,36]. In the particular case of the use of Information and Communication Technologies (hereinafter ICT), they are able to reduce transaction costs, improving the efficiency of business activities across the value chain [37].…”
Section: Contextual Framework and Working Hypothesismentioning
confidence: 99%
“…From a theoretical perspective, in line with what has been argued by several scholars (Moulaert et al, 2005;Neumeier, 2012;Rover et al 2016), Italian PGS schemes are a valuable example of niches of social innovation that apply an approach of civic involvement and social change by solving social needs and adopting contextually productive practices that preserve the environment. These findings have proven the outstanding role of PGS in shortening the supply chain and enhancing the value chain.…”
Section: Discussionmentioning
confidence: 70%
“…While some research has documented an increasing interest in the issue of locally based and participatory strategies for guaranteeing organic foods (Zanasi et al, 2009;Nelson et al, 2010Nelson et al, , 2016Sacchi, 2011;2015;Sacchi et al 2015;Demartini et al, 2016;Rover et al, 2016;Home et al, 2017), there currently exists no single study focusing on analyzing participatory quality assurance systems in Italy. Analyzing the experience in Italy is of particular importance since Italy is the first Western country to admit the value of PGS by issuing Regional Law no.…”
Section: Introductionmentioning
confidence: 99%
“…However, categories of analysis of social sustainability were not used. In the same vein, Rover et al [46] demonstrated the contributing role of a Brazilian agroecology network to social innovation and sustainable rural development, but used socioeconomic categories of sustainability.…”
Section: Rural Tourism and Sustainability In Collaborative Spacesmentioning
confidence: 99%